Cerebral venous sinus thrombosis in traumatic brain injury: A systematic review of its complications, effect on mortality, diagnostic and therapeutic management, and follow-up - Netteland, Dag Ferner; Sandset, Else Charlotte; Mejlænder-Evjensvold, Magnus; Aarhus, Mads; Jeppesen, Elisabeth; Aguiar de Sousa, Diana; Helseth, Eirik; Brommeland, Tor (Frontiers in Neurology, 2023)
Objective Cerebral venous sinus thrombosis (CVST) is increasingly being recognized in the setting of traumatic brain injury (TBI), but its effect on TBI patients and its management remains uncertain. Here, we systematically review the currently available evidence on the complications, effect on mortality and the diagnostic and therapeutic management and follow-up of CVST in the setting of TBI. Methods Key clinical questions were posed and used to define the scope of the review within the following topics of complications; effect on mortality; diagnostics; therapeutics; recanalization and follow-up of CVST in TBI. We searched relevant databases using a structured search strategy. We screened identified records according to eligibility criteria and for information regarding the posed key clinical questions within the defined topics of the review. Results From 679 identified records, 21 studies met the eligibility criteria and were included, all of which were observational in nature. Data was deemed insufficiently homogenous to perform meta-analysis and was narratively synthesized. Reported rates of venous infarctions ranged between 7 and 38%. One large registry study reported increased in-hospital mortality in CVSP and TBI compared to a control group with TBI alone in adjusted analyses. Another two studies found midline CVST to be associated with increased risk of mortality in adjusted analyses. Direct data to inform the optimum diagnostic and therapeutic management of the condition was limited, but some data on the safety, and effect of anticoagulation treatment of CVST in TBI was identified. Systematic data on recanalization rates to guide follow-up was also limited, and reported complete recanalization rates ranged between 41 and 86%. In the context of the identified data, we discuss the diagnostic and therapeutic management and follow-up of the condition. Conclusion Currently, the available evidence is insufficient for evidence-based treatment of CVST in the setting of TBI. However, there are clear indications in the presently available literature that CVST in TBI is associated with complications and increased mortality, and this indicates that management options for the condition must be considered. Further studies are needed to confirm the effects of CVST on TBI patients and to provide evidence to support management decisions. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier: PROSPERO [CRD42021247833].